Conceptual design of DALS test facility cryogenic system. Issue 1 (1st May 2022) - Sun, Z; Huang, L; Shi, X; Wang, XL
Abstract: Dalian advanced light source (DALS) is a new project proposed by Dalian Institute of Chemical Physics (DICP) aiming to produce high-quality electron beam with repetition rate up to 100 kHz and the project is subject to central government approval. The cryomodules and superconducting cavities need to be tested before assembled in the real accelerator so the test facility is necessary. The Accelerator module test facility (AMTF) project has been funded by Dalian local government and is currently under construction as the pre-research project for DALS, it consists of four testbenches, one Horizontal testbench (HTB) for cryomodule test, one Vertical testbench (VTB) for cavity test, one Cryogenic testbench (CTB) for cryogenic test and one Injector testbench (ITB) for beam test. A Test facility cryoplant (TFCP) with capacity of 370 W@2 K will be used for cooling testbenches. This paper presents the design and current progress of the TFCP system, which includes the refrigerators, helium compressors, process vacuum pump system (PVPS), gas storage system, recovery and purification system.